Association between LGR5 Expression and Overall Survival in Patients with Colorectal Cancer: A Retrospective Study from Indonesia - Suhendra, Edward Julio; Warsinggih, Warsinggih; Kusuma, Muhammad Ihwan; Mappincara, Mappincara; Prihantono, Prihantono; Hendarto, Joko; Masadah, Rina; Faruk, Muhammad (Asian Pacific Journal of Cancer Biology, 2025)
Background: Leucine-rich repeat-containing G-protein-coupled receptor 5 (LGR5), also known as GPR49, is a Wnt signaling target that plays an important role in colorectal carcinogenesis and is often associated with poor prognosis in patients with colorectal cancer. Aim of this study was to assess the influence of LGR5 expression and its relationship with overall survival (OS) in colorectal cancer. Material and methods: This retrospective study assessed LGR5 expression via immunohistochemistry (IHC) in 30 archival colorectal cancer tissue samples from patients resected between 2019-2020 in Makassar, Indonesia. The association between LGR5 expression levels (high vs. low) and overall survival (OS) was analyzed. Result: Research results were obtained from 30 samples. Overall, 8 patients with high LGR5 expression and 22 patients with low LGR5 were reported. Among the total number of patients enrolled, 22 patients had an OS of 3 years and 8 patients had an OS of 5 years. Statistical analysis showed that there was no association between LGR5 expression and the clinical profile of colorectal cancer patients (p-value > 0.05). A statistically significant association between OS and both tumor stage and histopathological grading (p-value <0.001 and 0.016, respectively) was found. However, no statistically significant association between OS and LGR5 expression was observed (p-value 0.418). Conclusion: LGR5 expression was not associate with either OS and or clinical characteristics of CRC patients in Makassar, Indonesia. However, there was a tendency for low LGR5 expression to be associated with improved OS, although this finding was not statistically significant. Both tumor stage and histopathological grading were associated with OS.